Methods for Lipid Droplet Biophysical Characterization in Flaviviridae Infections - Martins, Ana S.; Martins, Ivo C.; Santos, Nuno C. (Frontiers in Microbiology, 2018)
Lipid droplets (LDs) are intracellular organelles for neutral lipid storage, originated from the endoplasmic reticulum (ER). These organelles are composed by a neutral core of triacylglycerols and sterol esters, surrounded by a monolayer of phospholipids and cholesterol, with several proteins at the surface. LDs play a central role in cellular energy storage and lipid metabolism. Viruses from the Flaviviridae family, namely dengue virus (DENV), hepatitis C virus (HCV), West Nile virus and Zika virus, interact with LDs to usurp the host lipid metabolism for their own viral replication and pathogenesis. Flaviviruses have a similar structure, with a lipid bilayer, where the envelope and membrane proteins are located, surrounding the nucleocapsid. The nucleocapsid contains the RNA genome complexed with multiple copies of the capsid protein. During viral replication, these positive-sense RNA viruses hijack the infected cell intracellular membrane machinery, increasing the number of host intracellular LDs and their diameter. LDs are targeted by several viral proteins and play multiple roles during the viral life cycle. The core and capsid protein, of HCV and DENV, respectively, extensively interact with LDs to regulate essential steps for their replication and assembly. In fact, flaviviruses use their viral proteins to regulate viral RNA replication through the interaction with LDs-surface proteins and use LDs, near the endoplasmic reticulum, as platforms for virus assembly. A lack of knowledge of key viral life cycle steps, such as assembly and encapsidation, is one of the reasons for the absence of effective vaccines or specific therapeutics against important pathogens from the Flaviviridae family. Detailed studies of LDs and their interactions with viral factors are crucial for the development of possible inhibitors of these key steps of viral replication. Microscopy studies have been the approach commonly used to observe LDs accumulation and localization in infected cell cultures. However, there are other approaches that enable the study of these organelles in terms of size, surface charge and molecular interactions. Here, we review different biophysical techniques that can be used to extract this information, as well as approaches to isolate and purify LDs from a cell culture.